Environmental regulation stringency and foreign direct investment. (23rd February 2022) - Tran, Quan; Tran, Thao; Vo, Duc Hong
Abstract: The effects of environmental regulation stringency on foreign direct investment are noted in the existing literature. However, current literature appears to have ignored the feedback effects from foreign investment to environmental regulation stringency. This feedback effect plays a significant role in designing policies to attract foreign investment to support economic growth and improve environmental quality concurrently. This study examines the feedback effects from foreign investment on environmental regulation stringency using the Organisation for Economic Co‐operation and Development (OECD) newly developed Environmental Policy Stringency Index for 26 OECD countries for almost three decades since 1990. The key findings from this study to the existing literature are threefold. First, we find that foreign investment affects the environment regulation stringency via lobbying. However, when the number of legislative units in the host countries is large enough, the lobbying effect diminishes, particularly for the larger‐gross domestic product (GDP) and the higher‐per‐capita‐income OECD countries. Second, our empirical results confirm the U‐shaped relationship between manufacturing activities and the environmental regulation stringency. Third, the bilateral relationship between environmental regulation stringency and foreign investment is found, indicating that ignoring foreign investment in designing environmental policies is problematic. Finally, policy implications have emerged based on the findings from this study.